Model Pelayanan Misi Holistik dalam Pengentasan Kemiskinan - Eunike Agoestina (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2019)
Poverty is a major problem for many countries in Asia and also in Indonesia. Until the end of 2017 the poverty rate in Indonesia has reached 10, 12%. Poverty is the condition of a person or group of people who do not have the ability to fulfill their basic needs, namely sadang, food, shelter, education, health properly because of low income, being in an oppressed state, and pressure in a community structure. The causes of poverty include many things, ranging from physical, psychological, moral, environmental, political and so on. Holistic mission is the preaching of the Gospel to realize God's shalom to humans as a whole body, spirit, in relation to the environment, social, political, and economic which cannot be separated from one another. Poverty is a human problem that does not bring God's shalom, so a holistic mission becomes a mission model that can answer and be a solution to the problem of poverty. The holistic mission model action that can be taken in efforts to alleviate poverty is the assistance of basic needs, interventions on government policies, opening training and employment for poor families. Abstrak IndonesiaKemiskinan menjadi masalah utama banyak negara yang ada di Asia dan juga di Indonesia. Sampai dengan akhir tahun 2017 Angka kemiskinan di Indonesia telah mencapai angka 10, 12%. Kemiskinan adalah keadaan orang atau sekelompok orang yang tidak memiliki kemampuan untuk memenuhi kebutuhan dasarnya yaitu sadang, pangan, papan, pendidikan, kesehatan secara layak karena pendapatan yang rendah, berada dalam keadaan tertindas, dan tekanan dalam suatu tatanan struktur masyarakat. Penyebab kemiskinan meliputi banyak hal, mulai dari keadaan fisik, psikis, moral, linkungan, politik dan sebagainya. Misi Holistik adalah pemberitaan Injil untuk mewujudkan shalom Allah kepada manusia secara menyeluruh tubuh, jiwa roh, dalam kaitannya dengan lingkungan, sosial, politik, ekonomi yang tidak bisa dipisah satu dengan yang lain. Kemiskinan adalah masalah manusia yang tidak mendatangkan shalom Allah, sehingga misi holistik menjadi suatu model misi yang bisa menjawab serta menjadi solusi bagi masalah kemiskinan. Aksi model misi holistik yang dapat dilakukan dalam upaya pengentasan kemiskinan adalah bantuan Kebutuhan pokok, intervensi terhadap kebijakan pemerintah, pembukaan pelatihan dan lapangan kerja bagi keluarga miskin.